Administration of tenofovir disoproxil fumarate-based antiretroviral therapy in an HIV-infected patient following unilateral nephrectomy. (August 2016) - Biagi, Mark; Badowski, Melissa; Chiampas, Thomas; Young, Jeremy; Vaughn, Pyrai; Shicker, Louis; Patel, Mahesh
Summary: We report the use of efavirenz 600 mg/emtricitabine 200 mg/tenofovir disoproxil fumarate 300 mg, once daily in a 47-year-old black man with a solitary kidney and human immunodeficiency virus (HIV). In 1990, he underwent radiation, chemotherapy, and ultimately, a unilateral nephrectomy for Wilms' tumor. Because of previous reports of tenofovir disoproxil fumarate-induced nephrotoxicity, our objective was to evaluate and monitor our patient's renal function over the course of 19 months based on serum creatinine, estimated creatinine clearance using the Cockroft-Gault equation, estimated glomerular filtration rate using the modification of diet in renal disease formula and urinalyses. After experiencing gastrointestinal side effects from other antiretroviral agents, our patient was switched to efavirenz/emtricitabine/tenofovir disoproxil fumarate in June 2013. At baseline, his serum creatinine was 1.35 mg/dL, estimated creatinine clearance 68.7 mL/min (based on actual body weight of 71.8 kg), estimated glomerular filtration rate 72.9 mL/min/1.73 m 2, with a CD4 cell count of 119 cells/mm 3 (5%) and an undetectable HIV viral load. In March 2015, his weight was 73.2 kg, serum creatinine 1.42 mg/dL, estimated creatinine clearance 65.2 mL/min, estimated glomerular filtration rate 68.1 mL/min/1.73 m 2, with a CD4 cell count of 120 cells/mm 3 (10%) and an undetectable HIV viral load. Other authors have reported tenofovir-induced nephrotoxicity in patients with a solitary kidney. Our patient had no evidence of nephrotoxicity over the course of 19 months on tenofovir disoproxil fumarate-based antiretroviral therapy (ART). He maintained adequate renal function, comparable to his baseline renal function. Our case report suggests that a tenofovir disoproxil fumurate-based ART may be a viable option for some patients with a solitary kidney. Additional studies and data are needed considering this is a small and relatively unstudied population.